Environmental behavior and analytical techniques of dissolved organic matter in groundwater systems: a review - Xianjiang Zeng; Ke Chen; Huifeng Yang; Qichen Hao; Ruifang Meng; Zhenzhou Sun; Zhonghao Jin (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Binocular-depth-guided dual-view camera-LiDAR fusion for kiwifruit pose estimation in robotic harvesting - Shiao Niu; Leilei He; Qilin Gong; Qichen Huang; Ruichao Luo; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Anastasia Grecheneva; et al. (Computers and Electronics in Agriculture, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Multi-omics reveals the host-gut microbiota interplay underlying divergent feed efficiency in grass carp (Ctenopharyngodon idella) fingerlings fed with high carbohydrate-to-protein ratio diet - Jinjuan Wan; Xiaoyan Xu; Qichen Jiang; Xiaolong Gu; Junjie Shao; Chongwan Liu; Menglin Sun; Aijun Xia; Jiale Li (Aquaculture, 2026)

The multi-faceted impacts of anthropogenic groundwater recharge on groundwater environment: A review - Chen Ke; Zeng Xianjiang; Hao Qichen; Yang Huifeng; Meng Ruifang; Sun Zhenzhou; Jin Zhonghao (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Unveiling the underlying mechanism: Metabolic reprogramming and oxidative stress mediate nanoplastic-induced hepatotoxicity in a freshwater fish (Pseudorasbora parva) - Sun Xu; Dan Wu; Qing Wang; Zihan Zhou; Qichen Jiang; Hong Shan; Haoran Zheng; Yuxi Shen; Ying Wang; Zizhou Wang (Aquatic Toxicology, 2026)

Assessment of vegetation carrying capacity at the basin-scale using an improved SWAT model - Shantao An; Yiping Wu; Xiankai Luo; Ziqi He; Sergey Kivalov; Georgii Alexandrov; Weiqin Dang; Wende Yan; Huanyuan Wang; Bellie Sivakumar; Guangchuang Zhang; Qichen Wang; et al. (CATENA, 2026)

Coupled dynamic modeling and analysis for collecting asteroid soil using a flexible brush sampler - Qichen Sun; Bolin Zhang; Bo Lei; Fan Guo; Jianfeng Man; Jinyang Liu; Zeng Zhao (Advances in Space Research, 2025)

A multi-site Ru-Cu/CeO2 photocatalyst for boosting C-N coupling toward urea synthesis - Qingyu Wang; Yangyang Wan; Qichen Liu; Yida Zhang; Zhentao Ma; Zirui Xu; Pengting Sun; Gongming Wang; Hai-Long Jiang; Wenping Sun; Xusheng Zheng (Science Bulletin, 2025)

Recent advances in integrating solvent-based CO2 capture with electrochemical regeneration process: A review - Peng Liu; Hanming Liu; Kangkang Li; Zian Fan; Qichen Lu; Beiqi Sun; Lin Hu; Ling Yin; Xiaolong Wang; Lianbo Liu (Fuel, 2025)

Artificial Intelligence in the Training of Radiology Residents: a Multicenter Randomized Controlled Trial - Yanqiu Chen; Zhen Sun; Wenjie Lin; Ziwei Xv; Qichen Su (Journal of Cancer Education, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Experimental investigation and theoretical modeling of cutting mechanics using serrated tines in drilling lunar regolith simulant - Yinliang Zhang; Riyue Wu; Zhiwei Long; Zeng Zhao; Lusi Wang; Guidong Mo; Qichen Sun; Kun Xu; Xilun Ding; Tao Zhang (Advances in Space Research, 2024)

Effect of different organic loads on the performance and microbial community mechanism of dry anaerobic digestion - Feng Zhen; Di Wu; Yongming Sun; Bin Qu; Lianhua Li; Ying Li; Qichen Li; Tao Xing (Fuel, 2024)

Slow intrusion experiments into granular media under microgravity - Fan Guo; He Zhang; Yang Yu; Bin Cheng; Qichen Sun; Zeng Zhao; Meng Zou; Xiaojing Zhang; Lei Lv (Advances in Space Research, 2024)

Molecular Characterization of Prdx Family and Response of Antioxidant Enzymes in Berberine Hydrochloride-Treated Charybdis japonica Infected With Aeromonas hydrophila - Mingming Han; Tianheng Gao; Yuxin Liu; Zakaria Zuraini; Chenxi Zhu; Tongqing Zhang; Feng Ji; Qichen Jiang; Xian Sun (Frontiers in Marine Science, 2021)
Berberine hydrochloride is an isoquinoline alkaloid, which has antitumoral, antibacterial, and antiviral activities in vivo and in vitro . Charybdis japonica is one of the main economic species of crab in Southeast Asia. We studied the molecular mechanism of oxidative stress in berberine hydrochloride-treated C. japonica infected with Aeromonas hydrophila . C. japonica were infected with A. hydrophila after being submerged in different concentrations (0, 100, 200, and 300 mg/L) of berberine hydrochloride for 48 h. The full-length cDNA of Prx6 and the ORFs of Prx5 and PXL2A were cloned. Prx6 and PXL2A each have one conserved domain, Cys44 , and Cys81 . The Prx5 conserved domain contains three important Cys loci, Cys75 , Cys100 , and Cys76 . Prx6 was different from Prx5 and PXL2A in the Peroxiredoxin family. The transcription levels of PXL2A infected with A. hydrophila were all higher than the control. The transcription levels of C. japonica were further increased by adding berberine hydrochloride and were increased the highest at a concentration of 300 mg/L. The activities of glutathione peroxidase, superoxide dismutase, and catalase in the hepatopancreas of berberine hydrochloride-treated C. japonica infected with A. hydrophila were significantly increased compared with those only infected with A. hydrophila and the control group. The glutathione transferase activity in the hepatopancreas was significantly increased in berberine hydrochloride-treated C. japonica . The results of this study provide a new understanding of the potential role of berberine hydrochloride on the oxidative stress mechanisms of C. japonica .